Avaliação da eficiência de vacinas contra Clostridium septicum - Liliane Dane Dias (2003)
Twelve commercial vaccines against clostridiosis were evaluated having in their composition Clostridium septicum toxoids and/or bacterial cells, have been evaluated for potency by mice serum neutralization tests using rabbit or bovine sera and challenge test in guinea-pig. The vaccines, coded as T1, T10 and T11, elicited alpha antitoxin titers in rabbits which were superior to the minimum test level of 2.5 lU/mL, as recommended for quality control, and the vaccines T2 and T4 eliciting titers of 2.0 and 2.5 lU/mL. Similar results were obtained as detected in bovine sera against vaccines T1, T2, T4 and T10. The T11 vaccine was not evaluated in bovines. According to the challenge tests in guinea pigs no vaccine met the minimum requeriments for approval. Clostridium septicum vaccines were in general inefficient for stimulating the immune response as evaluated by the recomendaded tests.